Investigation of sintering behavior of ZrO2 (Y) ceramic green body by means of non-isothermal dilatometry and thermokinetic analysis; Journal of Thermal Analysis and Calorimetry; Vol. 182, iss. 2 - Surzhikov A. P. Anatoly Petrovich; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Franguljyan T. S. Tamara Semenovna; Vasiljev I. P. Ivan Petrovich; Chernyavski (Chernyavskiy) A. V. Aleksandr Viktorovich (2017, 2017)
Title screen